Bioorthogonal Chemical Reporters for Selective In Situ Probing of Mycomembrane Components in Mycobacteria. (6th January 2016) - Foley, Hannah N.; Stewart, Jessica A.; Kavunja, Herbert W.; Rundell, Sarah R.; Swarts, Benjamin M.
Abstract: The global pathogen Mycobacterium tuberculosis and other species in the suborder Corynebacterineae possess a distinctive outer membrane called the mycomembrane (MM). The MM is composed of mycolic acids, which are either covalently linked to an underlying arabinogalactan layer or incorporated into trehalose glycolipids that associate with the MM non‐covalently. These structures are generated through a process called mycolylation, which is central to mycobacterial physiology and pathogenesis and is an important target for tuberculosis drug development. Current approaches to investigating mycolylation rely on arduous analytical methods that occur outside the context of a whole cell. Herein, we describe mycobacteria‐specific chemical reporters that can selectively probe either covalent arabinogalactan mycolates or non‐covalent trehalose mycolates in live mycobacteria. These probes, in conjunction with bioorthogonal chemistry, enable selective in situ detection of the major MM components.